Implementasi Undang-Undang Nomor 23 Tahun 2011 tentang Pengelolaan Zakat di Badan Amil Zakat Nasional Kabupaten Polewali Mandar - Salma S.; Jamaluddin (Al-Mizan (e-Journal), 2022)
This study aims to answer questions regarding zakat management strategies at the National Zakat Agency (Baznas) of Polewali Mandar Regency and the implementation of Law Number 23 of 2011 concerning Zakat Management at Baznas Polewali Mandar Regency. This research is qualitative-empirical research using a juridical-sociological and historical approach. Empirical legal research uses secondary data as initial data obtained from primary and secondary legal materials, then followed by primary data or field data obtained from documents, interviews, and observations. The results of the study show that the zakat management strategy at Baznas Polewali Mandar Regency is in line with the spirit mandated by Law Number 23 of 2011 concerning Zakat Management. These strategies are: collaborating with the Polewali Mandar Regency Government, conducting zakat outreach and education, collaborating with religious and community leaders, and forming a zakat collection unit (UPZ), so the implementation of the zakat law has been carried out properly.